Pengaruh Promosi, Harga, Kualitas Produk Terhadap Minat Beli Sepeda Motor Honda Di Kota Yogyakarta - Mustika Hakim (Program Studi Manajemen Fakultas Ekonomi UST, 2019)
Purchasing interest in consumers is a very important factor in marketing activities. There are several variables that can affect consumer buying interest, including promotions, prices and product quality. But the results of each study conducted by several researchers have different results. So this needs to be further investigated. This study aims to determine the effect of promotion, price and product quality on buying interest. The method used in this research is quantitative with multiple linear analysis, partial t test and coefficient of determination. Furthermore, the results of this study are that promotion does not affect buying interest, while the price and quality of products have a significant positive effect on buying interest.